Ta hand om dig! - Empatitrötthet, stöd och egenvårdsstrategier bland nyutexaminerade socionomer - Lantz,Thilde; Ohlsson,Catja (2025)
The purpose of the survey was to determine how social workers, with up to five years in their profession, perceive how compassion fatigue relates to organized support and self-care strategies. Addressing this question for our research, we conducted a quantitative study using bivariate correlation analysis. The results indicate that with higher levels of organized support and development combined with a daily balanced life and cognitive awareness, the risk of compassion fatigue can be reduced. Self-care strategies also prove that there is a connection to compassion satisfaction. This means that the more frequently self-care strategies are used, the happier and more satisfied newly graduated social workers feel in their work helping people.
Keywords: empatitrötthet; sekundär traumatisering; utbrändhet; medkänsletillfredställelse; egenvårdstrategier; coping. Keywords: Compassion fatigue; secondary trauma; burnout; compassion satisfaction; self-care; coping